Estabilidad de compuestos fenólicos y capacidad antioxidante, de una bebida alcohólica de cálices de Jamaica (Hibiscus Sabdariffa). - Escobar Vega, Bryan David (2023)
The purpose of this project is to determine the stability of phenolic compounds and antioxidant capacity, in an alcoholic beverage made from Jamaican calyxes (Hibiscus Sabdariffa). During the fermentation process, dehydrated and fresh calyxes cultivated by the company SERVIFUMIAGRO S.A. were used. in the city of Loja- Ecuador, where the physical-chemical parameters were determined, as well as the content of total phenols by the Folin-Ciocalteu method with a wavelength of 764 nm and the antioxidant capacity by the 2,2-Difenil-1-Picrilhidrazilo method with a length 516 nm waveform, samples were collected every 5 days from the start of fermentation to day 15, having a total of 24 samples, the factors studied are Factor A: Dehydrated calyxes, fresh calyxes and Factor B: Fermentation time periods (1 day, 5 days , 10 days and 15 days). For the elaboration of this project, an experimental design was applied under an AxB factorial arrangement, it was registered for data processing in the Statgraphics Version 16.1.03 software, whose results were: For the alcoholic beverage from dried Jamaican calyxes, the soluble solids on day one are 21.5 ± 0.01* ºBrix and on day fifteen 12.3 ± 0.02* ºBrix, its pH on day one is 2, 7 and on day 15 of 2.3, the total phenols on the first day is 72.12 mg EAG/ml and on day 15 it is 71.56 mg EAG/ml and the antioxidant capacity on the first day is 106.24. %DPPH and for day 15 104.01% DPPH is recorded, while for the alcoholic beverage with fresh calyxes from Jamaica the soluble solids on the first day is 22.6 ± 0.01* ºBrix and for day 15 a 13.9 ± 0.01* ºBrix is registered, the pH starts with a 3.9 and ends with 3.6, for the content of total phenols on the first day a 53.37 mg EAG/ml is registered and ends on day 15 with a 52.01 mg EAG/ml and in the antioxidant capacity in the first day 92.06% DPPH is recorded and ends with 90.12% DPPH, with these results it indicates that the stability of phenolic compounds and antioxidant capacity decreases in the fermentation process